Calibrating Leaf Colour Chart For Optimal Fertilizer Nitrogen Management In Basmati Rice Under Temperate Conditions Of Kashmir (Applied Biological Research, 2016)
Field experiments were conducted in 2013 and 2014 with the aim to  develop optimal nitrogen management for Basmati rice cv. ‘Pusa  Sugandh-3’ using leaf colour chart (LCC). The treatments included no  nitrogen (N0) treatment, three fixed time (60, 90 and 120 kg N ha-1) and  four real time nitrogen management treatments. Grain and straw yield,  total N uptake and various indices of N use efficiency were measured in  both the years. The best response in all the parameters assessed was  achieved with LCC treatments maintained at 20 kg N ha-1 (LCC 420) and  30 kg N ha-1 (LCC 430) . However, LCC 420 treatment had significantly  higher nitrogen use efficiency (NUE) as compared to LCC 430 treatment  because the nitrogen applied in former treatment was 20 kg ha-1 lesser  than the later, while as yield in both the treatments was same. Based on  the principle that threshold value is the one which simultaneously  optimizes grain yield and NUE, LCC 420 treatment was adjudged as  threshold value for real time N management in Basmati rice variety  ‘Pusa Sugandh-3’ under temperate conditions of Kashmir.
Keywords: Basmati rice; LCC; nitrogen; N- use efficiency; yield